PSYCHOLOGICAL WELL-BEING AND QUALITY OF LIFE AMONG PHYSICALLY DISABLED AND NORMAL EMPLOYEES: Psychological Well-Being Among Physically Disabled - Kanwal, Hira; Mustafa, Nazia (Pakistan Armed Forces Medical Journal, 2016)
Objective: To study the relationship between psychological well-being and quality of life among employees and to see group differences on study variables between physically disabled and normal employees.Study Design: Cross sectional study.Place and Duration of Study: This study was carried out at General Headquarters, 501 & 502 Central Electrical and Mechanical Engineering Workshops Rawalpindi. It was conducted over a period of two months from April to May 2015.Subjects and Methods: Total sample size was 150 male employees in which 75 were physically disabled (69 polio affected, 4 deaf and dumb and 2 visually impaired) and 75 were normal employees from military organization/establishments. Affectometer-2 (Naheed, 1997) and WHOQOL-BREF (Khan, Akhter, Ayub & Laghari, 2003) were used to study psychological well-being and quality of life.Results: Results showed significant positive correlation between psychological well-being (combination of feeling good and functioning effectively) and quality of life and negative relationship with disability of employees. Group differences were seen that normal employees have high psychological well-being (t=5.90, p